2013
DOI: 10.1007/s10578-013-0428-0
|View full text |Cite
|
Sign up to set email alerts
|

Insecure Attachment Attitudes in the Onset of Problematic Internet Use Among Late Adolescents

Abstract: Studies on the role played by attachment attitudes among late adolescents who show Problematic Internet Use (PIU) are still lacking. Three self-report measures concerning attachment attitudes, childhood experiences of abuse, and Internet addiction were administered to 310 students (49 % males) aged 18-19 attending the last year of high school. Students who screened positive for PIU were more likely to be male and to have suffered childhood experiences of physical and sexual abuse; they also scored higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
89
2
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(108 citation statements)
references
References 42 publications
11
89
2
6
Order By: Relevance
“…Most of the time children are often alone since both parents work, spending a lot of time watching TV and playing video games. Some of them show problematic internet use and insecure attachment dispositions (Schimmenti, Passanisi, Gervasi, Manzella, & Famà, 2013;Schimmenti, Passanisi, Pace, Manzella, Di Carlo & Caretti, 2014) and are at risk of "freezing" their collective creativity and developing maladaptive attitudes and emotions that weaken the personality and reduce the capability to face daily problems (for clinical aspects, . Today schools are moving vertically by focusing only on the individual knowledge of the students, but it should also move transversely, promoting networks of relationships in the classroom setting, encouraging discussion and the exchanging of ideas and non verbal communication, in order to implement both creativity and interpersonal competencies, creating the basis for a divergent thinking not only at the individual level, but also in the class as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the time children are often alone since both parents work, spending a lot of time watching TV and playing video games. Some of them show problematic internet use and insecure attachment dispositions (Schimmenti, Passanisi, Gervasi, Manzella, & Famà, 2013;Schimmenti, Passanisi, Pace, Manzella, Di Carlo & Caretti, 2014) and are at risk of "freezing" their collective creativity and developing maladaptive attitudes and emotions that weaken the personality and reduce the capability to face daily problems (for clinical aspects, . Today schools are moving vertically by focusing only on the individual knowledge of the students, but it should also move transversely, promoting networks of relationships in the classroom setting, encouraging discussion and the exchanging of ideas and non verbal communication, in order to implement both creativity and interpersonal competencies, creating the basis for a divergent thinking not only at the individual level, but also in the class as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies on attachment types and various addictions have increased (Schimmenti et al, 2014). In Korea, studies on the relationship between attachment type, internet addiction, and smartphone addiction were conducted on adolescents and college students.…”
Section: ) Experience Of Close Relationship-revised (Ecr-r)mentioning
confidence: 99%
“…A sensitivity to SNS such as Facebook of anxiously attached invidividuals can predict more expressive and attention seeking behavior (Hart et al, 2015). In a study on peer attachment and SNS addiction, it was found that children and adolescents with poor peer attachment tend to depend on artificial objects, like the mobile (Schimmenti et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The internalization of unworthy or abusing parents (18) may also play a role in causing such emotion together with dysfunctional attitudes (i.e. insecure attachment and problematic internet use) (19,20) and disadaptive disorders (i.e. psychopathic traits) (21).…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%